1996
DOI: 10.1071/ea9960259
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition during fetal life alters annual wool production and quality in young Merino sheep

Abstract: The effect of maintenance v, submaintenance diets of pregnant ewes in 1991 and 1992 on establishment of the wool follicle population in their progeny, and its effect on the progeny's wool production (quantity, quality and variation across the body of the animal) to 1.4 years of age was examined. The experimental protocol used cloned animals created by bisecting embryos at day 6 of pregnancy. Each clone was placed in a ewe, which was subsequently fed from about day 50 to 140 of pregnancy at maintenance or subma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…This is consistent with the findings of Schinckel and Short (1961), Everitt (1967) and Kelly et al (1996). The high repeatability and small errors about the coefficients across years and sites (Tables 6-9) confirms the goodness of fit and predictability of the relationships derived in this study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with the findings of Schinckel and Short (1961), Everitt (1967) and Kelly et al (1996). The high repeatability and small errors about the coefficients across years and sites (Tables 6-9) confirms the goodness of fit and predictability of the relationships derived in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The development of the follicle population in the fetus is influenced by the nutrition of the ewe (Short 1955b;Schinckel and Short 1961;Everitt 1967). Progeny born to underfed ewes may grow less wool that is broader than progeny born to ewes that were better fed during pregnancy (Denney 1990;Kelly et al 1996Kelly et al , 2006. Kelly et al (1996) showed that in comparison to progeny from single-bearing ewes fed to maintain maternal liveweight during pregnancy, genetically identical progeny from ewes fed to lose 10 kg between Days 50 and 140 of pregnancy produced~0.14 kg less clean wool that was alsõ 0.1-mm broader at their hogget shearing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjustment factors for Great Southern WA and southern NSW were 8.5 for singles and 2.0 for twins, whereas these adjustment factors were double these values for south-west Vic. The impacts of the adjustments are shown in Tables 6-8. The adjustment in progeny wool production was based on hogget data and applied to all age groups of progeny because the weight of evidence supports that the progeny effects are permanent (Kelly et al 1996(Kelly et al , 2006Thompson et al 2011a). The production of the ewe component of the flock was also adjusted, because those animals are the progeny of the ewes from the previous generation, and it is assumed that the nutrition strategy for the ewes has been applied and the flock has achieved a steady state.…”
Section: Medium Wool Merinomentioning
confidence: 99%
“…Complications also arise in later life: human epidemiological studies reveal an increased predisposition to infertility (Ibnaez et al, 2000), cardiovascular disease and non-insulin-dependent diabetes in adults born with a low-birth weight (Barker, 1995). In sheep, unsuitable maternal nutrition during pregnancy can compromise future wool (for review, see Black, 1983;Kelly et al, 1996) and carcass quality (for review, see Bell, 1992) and reproductive performance (Gunn et al, 1995; for review, *Correspondence Email: dcwathes@rvc.ac.uk see Rhind et al, 2001). The term 'fetal programming' is used to describe such permanent alterations in fetal development (for review, see Barker and Clark, 1997;McMillen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%